2020
DOI: 10.3390/pr8020246
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of New Schiff Base/Thiol-Functionalized Mesoporous Silica: An Efficient Sorbent for the Removal of Pb(II) from Aqueous Solutions

Abstract: A new type of silica hybrid material functionalized with Schiff base-propyl-thiol and propyl-thiol groups (adsorbents 1 and 2, respectively) was synthesized using a co-condensation method. The synthesized materials and their starting materials were successfully characterized using a variety of techniques such as Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), X-ray diffraction (XRD), nitrogen adsorption–desorption isotherms, the Brunauer–Emmett–Teller (BET) surface area calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…First, it can be observed that the Schiff base and O-H stretching groups located at B3400 cm À1 overlap and increase with the ageing time. 51 This can have the following origins: (i) the presence of glyoxylic acid in water, in which the carbonyl converts to a geminal diol (two hydroxyl O-H functional groups bound to the same carbon) 52 and (ii) the reaction of chitosan and glyoxylic acid leading to a Schiff base 53 (imines with a characteristic CQN bonds) formation, which is accompanied by the formation of H 2 O molecules. According to the literature, the Schiff base is present between 3200 and 3400 cm À1 .…”
Section: Gel Electrolyte Solution Characterizationmentioning
confidence: 99%
“…First, it can be observed that the Schiff base and O-H stretching groups located at B3400 cm À1 overlap and increase with the ageing time. 51 This can have the following origins: (i) the presence of glyoxylic acid in water, in which the carbonyl converts to a geminal diol (two hydroxyl O-H functional groups bound to the same carbon) 52 and (ii) the reaction of chitosan and glyoxylic acid leading to a Schiff base 53 (imines with a characteristic CQN bonds) formation, which is accompanied by the formation of H 2 O molecules. According to the literature, the Schiff base is present between 3200 and 3400 cm À1 .…”
Section: Gel Electrolyte Solution Characterizationmentioning
confidence: 99%
“…It was reported that chitosan Schiff bases have excellent chelation ability with heavy metal ions, because it can act as a good binding site for many transition metals and therefore can form stable coordination complexes [12,13]. In azomethine derivatives, the C = N linkage is essential for biological activity; several azomethines were reported to possess remarkable antibacterial, antifungal, anticancer, and diuretic activities.…”
Section: Introductionmentioning
confidence: 99%
“…The particle size, pore size and porosity percentage were determined by using ImageJ software from imaging FESEM results. [28][29][30] F I G U R E 4 Field emission scanning electron microscopy (FESEM) images of (A) MMO, (B) MMAO1, (C) MMAO2, and (D) MMAO3.…”
Section: Fesem-edx Analysismentioning
confidence: 99%
“…Figure9represented the CV curves for un-doped and Al-doped at scan rate of 50 mV s −1 with potential window of 0 -3 V for 5 cycles in 1 M MgTf 2 electrolyte. Ahmed et al and Venkataraman et al proved that the technique of three electrodes for CV setup using liquid electrolyte containing fluoride element shown the promising good result although they run with high scan rate of 50 mV s −1 and 100 mV s −1 in room temperature 29,30. CV curve belongs to MMO sample and represents the oxidation and reduction curves with overlapping cycles.…”
mentioning
confidence: 99%